Bayesian Repeated Games and Reputations - Francoise Forges; Antoine Salomon (Center for Economic Studies and ifo Institute (CESifo), 2014)
Under appropriate assumptions (private values and uniform punishments), the Nash equilibria of a Bayesian repeated game without discounting are payoff-equivalent to tractable, completely revealing, equilibria and can be achieved as interim cooperative solutions of the initial Bayesian game. This characterization does not apply to discounted games with patient players. In a class of public good games, the set of Nash equilibrium payoffs of the undiscounted game can be empty, while limit (perfect Bayesian) Nash equilibrium payoffs of the discounted game, as players become infinitely patient, do exist. These equilibria share some features with the ones of multi-sided reputation models.
Keywords: C73; C72; C71; D82; H41; 330; Bayesian game; incentive compatibility; individual rationality; infinitely repeated game; private values; public good; reputation